Amorphous TiO2 Shells: A Vital Elastic Buffering Layer on Silicon Nanoparticles for High‐Performance and Safe Lithium Storage. Issue 48 (4th April 2017) - Yang, Jianping; Wang, Yunxiao; Li, Wei; Wang, Lianjun; Fan, Yuchi; Jiang, Wan; Luo, Wei; Wang, Yang; Kong, Biao; Selomulya, Cordelia; Liu, Hua Kun; Dou, Shi Xue; et al.
Abstract: Smart surface coatings of silicon (Si) nanoparticles are shown to be good examples for dramatically improving the cyclability of lithium‐ion batteries. Most coating materials, however, face significant challenges, including a low initial Coulombic efficiency, tedious processing, and safety assessment. In this study, a facile sol–gel strategy is demonstrated to synthesize commercial Si nanoparticles encapsulated by amorphous titanium oxide (TiO2 ), with core–shell structures, which show greatly superior electrochemical performance and high‐safety lithium storage. The amorphous TiO2 shell (≈3 nm) shows elastic behavior during lithium discharging and charging processes, maintaining high structural integrity. Interestingly, it is found that the amorphous TiO2 shells offer superior buffering properties compared to crystalline TiO2 layers for unprecedented cycling stability. Moreover, accelerating rate calorimetry testing reveals that the TiO2 ‐encapsulated Si nanoparticles are safer than conventional carbon‐coated Si‐based anodes. Abstract : Commercial silicon nanoparticles encapsulated by amorphous titanium oxide (TiO2 ), with a core–shell structure, deliver superior electrochemical performance and high‐safety lithium storage. The amorphous TiO2 shells can offer superior buffering properties and achieve excellent lithium‐storage properties with high initial Coulombic efficiency, long‐term cycling stability, and greater safety.